The Effect of Nutrinest Application-Based Feeding Rules Education on the Nutritional Status of Toddlers - Sarah Rahmania; Syamsul Anwar; Titin Sutini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Toddlers are an age stage that is vulnerable to malnutrition. This is due to the lack of understanding of mothers about feeding rules which affects feeding practices. NutriNest application based feeding rules education can increase maternal knowledge in improving the nutritional status of toddlers. This study aims to analyze the effect of feeding rules education based on the NutriNest application on the Nutritional status of toddlers. The research method is a quasi-experimental pre-post test control group with repeated measures with purposive sampling technique of 40 mothers who have toddlers. Respondents are divided into two groups, namely intervention and control. Measurement of toddler nutritional status is carried out every week for 1 month, both before and after the intervention based on BB/TB then converted into a z-score values. Data analysis used the Mann-Whitney bivariate test and GLM-RM multivariate analysis. The results showed that there was an average difference between the intervention and control groups of 14.55 with a p-value of 0.000 (<0.05). The difference in nutritional status of toddlers in the intervention group was seen in the 4th measurement (1 month of intervention) with a p-value of 0.027 (<0.05). It can be concluded that there is an effect of providing feeding rules education on the nutritional status of toddlers at the Cipondoh Health Center, Tangerang City. The NutriNest application-based feeding rules education program is expected to be integrated into health services as an effort to prevent malnutrition and improve the nutritional status of toddlers.